SoTL enculturation guided by Kotter's model of change. Issue 4 (2nd October 2021) - Chen, Chwen Jen
ABSTRACT: This paper describes how various initiatives to develop SoTL culture can be inspired by the eight steps of Kotter's model of organizational change. The purpose of each step is to provide a set of probing questions for institutional leaders, academic developers, and faculty leaders on their roles to support this enculturation. Mapping Kotter's steps with this list of questions and potential initiatives may guide the process of weaving SoTL into a university's teaching and learning culture.